Local metallicity in simulated galaxies - Collacchioni, Florencia (2021)
In the last decade, integral field spectroscopy has expanded our understanding of chemical evolution of galaxies, giving evidence of a radial gradient of gas-phase metallicity. In this work, we use the state-of-art hydrodynamical simulation EAGLE to study the resolved, local properties of galaxies. We show that the local gas metallicity correlates with the stellar mass surface density and anti-correlates with the gas accretion. Resolved metallicity profiles acts as a good estimator of gas accretion, and can be used to understand the changes in the chemical enrichment of galaxies.